2003
DOI: 10.1007/s000110300021
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin alleviates bronchoconstriction and airway hyperreactivity in ovalbumin sensitized mice

Abstract: Our study showed that luteolin treatment during and after sensitization significantly attenuated the asthmatic features in experimental mice. Therefore, luteolin could be used either as a lead molecule to identify an effective antiasthma therapy or as a means to identify novel anti-asthma targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 12 publications
2
24
1
1
Order By: Relevance
“…Luteolin has been predicted to exert its anti-asthmatic effects by acting as an anti-inflammatory drug25373839. However, we found that luteolin strongly inhibited GABA A R-mediated responses in lung epithelia cells.…”
Section: Discussioncontrasting
confidence: 51%
“…Luteolin has been predicted to exert its anti-asthmatic effects by acting as an anti-inflammatory drug25373839. However, we found that luteolin strongly inhibited GABA A R-mediated responses in lung epithelia cells.…”
Section: Discussioncontrasting
confidence: 51%
“…The cytokines IL-4 and IL-5 were measured in BAL fluid supernatant and OVA-specific IgE levels in sera were measured by enzyme-linked immunosorbent assay (ELISA), as described previously [14, 19]. Corticosterone in the BAL fluid was assessed using an ELISA kit obtained from Neogen (USA).…”
Section: Methodsmentioning
confidence: 99%
“…There is an intense need to identify new molecules preferably from natural origin with negligible or no adverse effects for treating this epidemic disease. In view of this, several herbal compounds such as curcumin, luteolin, glycyrrhizin, verprosides and cannabinoids have been identified as anti-asthmatic agents in animal models of asthma [13,14,15,16,17], and efforts are still continued to search other potent herbal molecules. Based on its anti-inflammatory activity [5, 6], we speculated that CBX may also possess anti-asthmatic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an epidemiologic study found that a higher intake of flavonoids was associated with a lower incidence of asthma [44]. In experimental models, oral administration of flavonoids has been demonstrated to prevent allergic diseases including asthma, anaphylaxis, food allergies and atopic dermatitis [16, 17,32,33,34,35,36,37]. This study showed that the ocular symptoms were reduced in the EMIQ group.…”
Section: Discussionmentioning
confidence: 71%
“…We and others have shown that some kinds of flavonoids including apigenin, fisetin, luteolin and quercetin suppress the expression of Th2-type (IL-4, IL-5 and IL-13) [13, 14], proinflammatory cytokines [31] and CD40 ligand [15] in basophils or in mast cells. In addition to these in vitro antiallergic activities, studies with allergic animal models have demonstrated that flavonoids exert preventative and therapeutic effects by modifying Th2-type cytokine expression and suppressing IgE elevation [16, 17,32,33,34,35,36,37]. In our study we measured the serum levels of cytokines and chemokines before and after the study but found no significant reduction in Th2 cytokines (IL-4, IL-5 and IL-13), chemokines (eotaxin) or IgE concentration as a result of EMIQ intake except for TARC (fig.…”
Section: Discussionmentioning
confidence: 99%